2003
DOI: 10.1021/bp025609d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and Prolongation of Baculovirus‐Mediated Expression in Mammalian Cells: Focuses on Strategic Infection and Feeding

Abstract: The baculovirus/insect cell system has been widely used for recombinant protein production. Since the finding that baculovirus was able to infect hepatocytes in 1995, various attempts to utilize baculovirus as a gene delivery vehicle into mammalian cells have been reported. In this study, we intended to explore the possibility of utilizing a baculovirus/mammalian cell system as a nonlytic, continuous protein production system. A recombinant baculovirus vector carrying enhanced green fluorescent protein (EGFP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…It has been reported that the addition of baculovirus to mammalian cells in mid-log phase, followed by three further successive additions of virus (superinfection) at intervals of 3-4 days allows recombinant gene expression to be prolonged for over 10-15 days without addition any enhancing chemical such as butyrate (Hu et al, 2003). However, in our present transduction conditions with the multigene-BacMam vector carrying the VSV-G and WPRE elements, repetitive transduction was not always needed for efficient generation of iPS cells (i.e.…”
Section: Efficiency Of Baculovirus-mediated Expression System For Indmentioning
confidence: 99%
“…It has been reported that the addition of baculovirus to mammalian cells in mid-log phase, followed by three further successive additions of virus (superinfection) at intervals of 3-4 days allows recombinant gene expression to be prolonged for over 10-15 days without addition any enhancing chemical such as butyrate (Hu et al, 2003). However, in our present transduction conditions with the multigene-BacMam vector carrying the VSV-G and WPRE elements, repetitive transduction was not always needed for efficient generation of iPS cells (i.e.…”
Section: Efficiency Of Baculovirus-mediated Expression System For Indmentioning
confidence: 99%
“…Baculoviruses have been shown to be an effective vehicle for the introduction of DNA sequences into mammalian cells since they neither replicate nor cause cytopathic effects (24). MeWo cells were transfected with pP-Oka9⌬M DNA and infected at 1, 2, 3, 4, or 5 days posttransfection with a recombinant baculovirus expressing ORF9 under the control of the HCMV-IE promoter.…”
Section: Vol 81 2007 Vzv Bac Clone For Analysis Of Orf9 Product 13203mentioning
confidence: 99%
“…The disadvantage of baculovirus is the transient nature of expression, which usually lasts for 7 days, then the expression declines rapidly. Nonetheless, the expression level can be enhanced and prolonged by superinfection (Hu et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%